2014
DOI: 10.17659/01.2014.0061
|View full text |Cite
|
Sign up to set email alerts
|

Meckel’s Diverticulum in Adults: A Preoperative Diagnostic Dilemma

Abstract: Abstract:Pre-operative diagnosis of Meckel's diverticulum may be overlooked, given the rarity of this pathology in adults. The clinical manifestations are similar to those of other abdominal pathologies. Diagnosis is further compounded by the fact that conventional imaging methods do not pick-up the obvious anomaly. We present a case of Meckel's diverticulum with fibrous umbilical band causing small bowel obstruction. Our aim of presentation is to highlight the role of diagnostic laparoscopy in preoperative di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Here we present a rare case in which volvulus developed due to twisting around a persisting umbilical remnant. A literature review of online publication showed two case reports of volvulus of Meckel's diverticulum in children [2,7,8]. Intussusception of Meckel's diverticulum leading to intestinal obstruction is common but very few cases of volvulus of Meckel's diverticulum have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a rare case in which volvulus developed due to twisting around a persisting umbilical remnant. A literature review of online publication showed two case reports of volvulus of Meckel's diverticulum in children [2,7,8]. Intussusception of Meckel's diverticulum leading to intestinal obstruction is common but very few cases of volvulus of Meckel's diverticulum have been documented.…”
Section: Discussionmentioning
confidence: 99%